PCNL in horseshoe kidney- the first experience at HUSM - Rajagopal, Sasikumar; Kamarulzaman, Mohd Nazli; Y, Maya; Z, Zaidi; AR, Mossadeq; MD, Mohd Ashraf; Rahman, Mohd Nor Gohar; Z, Mahamood; Hassan, S (Universiti Sains Malaysia, 2008)
Horseshoe kidney is one of the commonest congenital renal fusion anomalies with an incidence of 0.25% in general population. Disturbances in urine flow, drainage and concomitant infections promote stone formation is common. Percutaneous nephrolithotripsy (PCNL) in horseshoe kidney is a challenge due to its anatomical difference and thus a modified technique is needed. Hereby, we report our first experience with PCNL in this anomaly, a 55 year old with left staghorn renal calculi in a horseshoe kidney